2020
DOI: 10.3390/antibiotics9030109
|View full text |Cite
|
Sign up to set email alerts
|

Successful High-Dosage Monotherapy of Tigecycline in a Multidrug-Resistant Klebsiella pneumoniae Pneumonia–Septicemia Model in Rats

Abstract: Background: Recent scientific reports on the use of high dose tigecycline monotherapy as a “drug of last resort” warrant further research into the use of this regimen for the treatment of severe multidrug-resistant, Gram-negative bacterial infections. In the current study, the therapeutic efficacy of tigecycline monotherapy was investigated and compared to meropenem monotherapy in a newly developed rat model of fatal lobar pneumonia–septicemia. Methods: A Klebsiella pneumoniae producing extended-spectrum β-lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…53 Some studies have suggested that monotherapy with a high dose of tigecycline is safe and optimally effective and can improve the outcome. [53][54][55][56][57] Nevertheless, other opinions have…”
Section: Discussionmentioning
confidence: 99%
“…53 Some studies have suggested that monotherapy with a high dose of tigecycline is safe and optimally effective and can improve the outcome. [53][54][55][56][57] Nevertheless, other opinions have…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows that although both nanomedicines resulted in significantly improved therapeutic efficacy in terms of increased rat survival time compared with free AA139, survival of all infected rats was not achieved. In relation to this, it should be noted that the pneumonia-septicemia rat model used in this study is representative of multidrug-resistant bacterial infections that are associated with very high mortality rates in patients and are particularly challenging to treat successfully (38). Furthermore, there is published evidence that rats may be more sensitive to the innate immune activation known to be caused by AMPs, including histamine release (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains. The ESBL-positive strain K. pneumoniae ESBL EMC2003 (referred to in this publication as K. pneumoniae ESBL) used in this study has previously been characterized in terms of its genotype and antimicrobial susceptibility profile and was used to establish pneumonia-septicemia in rats (38). The stability of the plasmid-containing K. pneumoniae ESBL strain was confirmed through five consecutive passages in Mueller-Hinton II (MH-II) broth (Becton, Dickinson BV, Vianen, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each group, the dosage of substances used was the same: hBD-3 and Epi-1, 10 mg/kg; and meropenem, 25 mg/kg. Meropenem dosage was chosen in accordance with previous study of H. Van der Weide et al [ 41 ].…”
Section: Methodsmentioning
confidence: 99%